Conforto térmico e desempenho nos ambientes de ensino com inovações tecnológicas - estudo de multicasos no nordeste brasileiro - Torres, Manoel Geronimo Lino (2016)
Introduction: The global warming has severe environmental impacts and reach different areas and localities, in particular the least developed countries in the tropical region. In Brazil, the regions that suffer most impacts, with such changes will be the Amazon and Northeast. With the development of modern society, it is observed that individuals are consuming much of their time indoors, so, numerous studies have sought to study environmental comfort conditions to assist in the execution of activities and maximize human performance. One of the many changes that took place is in the learning environment, which is different compared to years ago. Technological resources in the classroom have made this a more versatile environment, allowing students and teachers to interact with other institutions, providing greater flexibility in the use of tools that extend their cognitive abilities. However, these tools can both facilitate communication and versatility of teaching and learning as increase the thermal load in the environment that already suffers direct influence of the external environment. In this sense, important to investigate how it is the variables of thermal comfort affect students' performance in climate-controlled learning environments provided these technologies. Objective: We analyzed the relationship between thermal comfort and performance of students in environments with technological innovations in areas of northeastern Brazil. Materials and Methods: Data were obtained during the experiments in the two institutions classrooms (A and B) of higher education located in Northeast Brazil. The Institution A is a private university in the city of João Pessoa- PB and the institution B is a public university in city of Teresina-PI. A total of 103 students of the engineering course participated, with one session per day, per class, on three consecutive days. The air temperature through the air conditioning was adjusted to 20ºC and 24ºC; the last day and is turned off the device to try to reach the value of 30 ° C. By heat stress meter TGD400 and microclimate station Babuc A, positioned in the center of the room recorded the parameters of the thermal environment. Cognitive abilities were assessed by the five events that make up the BPR-5 instrument, broken down for the three days of the experiment. Subjective and personal variables were evaluated in accordance with ISO7730/2005, through check list (thermal resistance of clothing) and scales of 4 points (Comfort) and 7 points (Sensation and Desire). With the results and data obtained were carried out simulations using the Generalized Linear Models (GLM) to verify the relationship between thermal comfort and performance. Results: At the institution A 42,9% of the first day of collection, where the temperature was in it 21,49ºC, indicated to be feeling slightly warm environment (+1) and 51,9% said that the place was comfortable (1). The PMV index of ISO7730/2005 indicated that the room was cold, with 57% of the vote between -1,5 and -2,5. On the second day, with an average temperature was 23,24ºC, about 58,1% of the students felt the thermally neutral environment (0) and 55,4% rated it as comfortable (1). The PMV index, on the second day, indicated that the room was slightly cold, with 87,8% of the vote between -0,5 and -1,5. On the third day the mean temperature was 27,49ºC and 41,9% of the rated as hot environment (+2) and finally, 35.1% VII of the evaluated local rated as slightly uncomfortable (2). The Middle Foretold vote indicated that the room was slightly hot on the third day, with 60.8% of votes ranging from +0,5 to +1,5. The institution B, on the first day of collection whose average temperature was 20,07ºC, about 50% of students reported feeling that the environment was slightly cold (-1) and 61.5% of students rated the environment as comfortable (1). The PMV index indicated that the environment was cold with 92% of the vote results were between -1,5 and -2,5. On the second day the average temperature was 33,72ºC and 59,3% of students said they felt the warm environment (+2) and 66,7% rated it as uncomfortable (3). Regarding the PMV 100% of the frequency of the votes indicated that the environment was rated as very hot (PMV> +2.5). On the third day with the average temperature 22,95ºC, about 73,3% of the students indicated that the thermal sensation was neutral (0) and the place was rated by 96,2% of the students as comfortable (1). The PMV index showed that 88,5% of the calculated votes of the students indicated that the site was slightly cold (-0,5 <PMV <-1,5). Using Generalized Linear Models, in particular the Ordinal Regression, was observed from the data of the two institutions, the performance is linked to subjective criteria, in particular the thermal sensation and the globe temperature. It was observed that the rise globe temperature in 1 ° C increases the chance of students pass a performance range lower to a higher 34% for situations where the wind chill is indicated as very hot. Final considerations: This study showed that there is a difference between what the standard ISO7730/2005 predicts what is actually reported by students in areas of the Brazilian Northeast, ie situations where the standard indicates discomfort students report being comfortable. It was also observed that subjective variables are important factors for a good cognitive performance of students.